The Importance of Antihypertensive and Lipid-Lowering Therapy in the Treatment of Patients with a New Coronavirus Infection COVID-19 - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
At the end of 2020, a new term “post-COVID-19 syndrome” appeared in the medical community. The prevalence of this syndrome reaches more than 30% among patients who have had COVID-19, and its duration can vary from 12 weeks to 6 months. One of the most severe consequences of COVID- 19 is the defeat of the cardiovascular system, which has a variety of mechanisms: dysregulation of the renin-angiotensin-aldosterone system; pathological systemic inflammatory response; direct action of the virus on the myocardium with the development of myocarditis; respiratory failure with hypoxia, leading to damage to cardiomyocytes; microvascular damage due to hypoperfusion, increased vascular permeability, angiospasm and the direct damaging effect of the virus on the endothelium of the coronary arteries; thrombotic complications due to the procoagulant and prothrombogenic effect of systemic inflammation. One of the most promising directions in the treatment and prevention of damage to the cardiovascular system in patients with hypertension who have undergone COVID-19 is the appointment of antihypertensive drugs that have the most pronounced organoprotective properties together with statins. The single pill combination of lisinopril, amlodipine and rosuvastatin is an effective drug that allows achieving not only adequate hypotensive and lipid-lowering effects, but also due to its pronounced organoprotective properties, to expect a reduction in cardiovascular risk and complications in patients who have suffered a new coronavirus infection caused by the SARS-CoV-2 virus.